2008
DOI: 10.1007/s00299-008-0562-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insect (Microdera puntipennis dzungarica) antifreeze protein MpAFP149 confers the cold tolerance to transgenic tobacco

Abstract: To elucidate the function of antifreeze protein from Microdera puntipennis dzhungarica for freezing stress tolerance in plant, the construct of MpAFP149 gene with the signal peptide sequence responsible for secreting the native MpAFP149 into the apoplast space under control of a cauliflower mosaic virus 35S promoter was introduced into tobacco by Agrobacterium tumefaciens-mediated transformation. The observation of immunogold localization by TEM (transmission electron microscope) showed that the heterologous M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The comparative rate of lipid peroxidation was assayed from the leaves of transgenic and non-transformed plants by determining the level of malondialdehyde (MDA) production after exposure to cold stress (4°C) for 48 h, using the thiobarbituric acid (TBA) method as described by Wang et al (2008) with slight modifications of our own. Leaf samples (0.1 g) were homogenized with a mortar and pestle in 5 ml of 0.5% (v/v) TBA solution in 10% trichloroacetic acid (TCA) and centrifuged at 12,000 g for 15 min at 4°C.…”
Section: Malondialdehyde Estimationmentioning
confidence: 99%
“…The comparative rate of lipid peroxidation was assayed from the leaves of transgenic and non-transformed plants by determining the level of malondialdehyde (MDA) production after exposure to cold stress (4°C) for 48 h, using the thiobarbituric acid (TBA) method as described by Wang et al (2008) with slight modifications of our own. Leaf samples (0.1 g) were homogenized with a mortar and pestle in 5 ml of 0.5% (v/v) TBA solution in 10% trichloroacetic acid (TCA) and centrifuged at 12,000 g for 15 min at 4°C.…”
Section: Malondialdehyde Estimationmentioning
confidence: 99%
“…Introduction of the hyperactive antifreeze proteins of insects into the genome of plants has the potential to achieve the latter. AFPs and/or IAPs from fish, insects, and plants have been successfully expressed in tomato, tobacco, potato, and Arabidopsis thaliana (Hightower et al 1991;Kenward et al 1993;Wallis et al 1997;Kenward et al 1999;Meyer et al 1999;Holmberg et al 2001;Wang et al 2008;Zhu et al 2010). In some systems, AFP expression in transgenic plants produced plants whose extracts exhibited low levels of thermal hysteresis (0.37°C/mg apoplastic protein by nanoliter osmometer, Holmberg et al 2001) and recrystallization inhibition in vitro (Worrall et al 1998), as well as reduced electrolyte leakage in leaves after freezing (Wallis et al 1997;Zhu et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…), and the freezing temperature of the whole plant without roots was lowered by 1-3°C depending on the freezing treatment method used. In a recent study, Wang et al (2008) expressed a beetle (Microdera puntipennis dzungarica) antifreeze protein in tobacco and showed decreased ion leakage, lower malondialdehyde content in the leaves, and improved cold tolerance at −1°C for 3 days.…”
Section: Introductionmentioning
confidence: 98%
“…Holmberg et al (2001) also reported antifreeze activity in applications with very low concentrations of AFPs. Wang et al (2008) reported that in order to transfer antifreeze protection to a plant, it is crucial to introduce AFPs into the apoplast space to confer an optimal antifreeze effect. This phenomenon occurs since ice forms preferentially in the apoplast where the solute concentration is the lowest.…”
Section: Introductionmentioning
confidence: 99%